Szemináriumok, intézetek, klinikák vezetői és szakelőadók a debreceni tudományegyetemen (1914–1950) - Mudrák, József (Gerundium, 2010)
Szemináriumok, intézetek, klinikák vezetői és szakelőadók a debreceni tudományegyetemen (1914–1950)